A randomized, double-blind study of SHP465 mixed amphetamine salts extended-release in adults with ADHD using a simulated adult workplace design. Issue 5 (4th July 2018) - Wigal, Timothy; Brams, Matthew; Frick, Glen; Yan, Brian; Madhoo, Manisha
ABSTRACT: Objectives : The objective of this paper was to evaluate the efficacy, duration of effect, and tolerability of SHP465 mixed amphetamine salts (MAS) extended-release versus placebo and immediate-release MAS (MAS IR) in adults with attention-deficit/hyperactivity disorder (ADHD). Methods : Adults with ADHD Rating Scale, Version IV (ADHD-RS-IV) scores ≥24 were randomized to SHP465 MAS (50 or 75 mg), placebo, or 25 mg MAS IR in a double-blind, three-period, crossover study using a simulated adult workplace environment. On the final day of each 7-day treatment period, efficacy was assessed for 16 h postdose. Primary efficacy analyses for Permanent Product Measure of Performance (PERMP) total score averaged across all postdose assessments and each postdose time point were conducted in the intent-to-treat population using a mixed linear model. Secondary end-points included PERMP problems attempted and answered correctly and ADHD-RS-IV scores based on clinician ratings of counselor observations using the Time Segment Rating System and participant self-report. Tolerability assessments included treatment-emergent adverse events (TEAEs) and vital signs. Results : Least squares mean (95% CI) treatment differences (combined 50/75 mg SHP465 MAS–placebo) significantly favored SHP465 MAS over placebo for PERMP total score averaged across all postdose assessments (18.38 [11.28, 25.47]; P  < .0001) and at each postdose assessment (all P  < .02). Nominal superiority of MAS IR over placebo for PERMP total score averaged across all postdose assessments was observed (nominal P  = .0001); treatment differences between SHP465 MAS and MAS IR were not significant (nominal P  = .2443). The two most frequently reported TEAEs associated with SHP465 MAS were insomnia (36.5%) and anorexia (21.2%). Mean increases in pulse and blood pressure with SHP465 MAS exceeded those of placebo. Conclusions : SHP465 MAS (combined 50/75 mg) significantly improved PERMP total score versus placebo, with superiority observed from 2 to 16 h postdose. The tolerability profile of SHP465 MAS was similar to previous reports of SHP465 MAS in adults with ADHD. Clinical trial registration : https://clinicaltrials.gov/ct2/show/NCT00928148 identifier is NCT00928148.